Glass beads from early medieval Ireland : classification, dating, social performance - Mannion, Mags, (Archaeopress archaeology., 2015)
This is a comprehensive study of glass beads from early medieval Ireland, presenting the national classification, typology, dating, symbology and social performance of glass beads.